Exploring the declining rates of state social work intervention in an English local authority using Family Group Conferences. (November 2019) - Sen, Robin; Webb, Calum
Abstract: Over the last decade England has seen rising numbers and rates of children in care and subject to child protection intervention. This article draws on national data and quantitative data from a study of 'City', a local authority in the north of England with a large Family Group Conference service. In distinction to national trends, City has seen substantial declines in the numbers and rates of children in care and who are subject to child protection intervention. The article analyses how notable these declines may be, comparing the declines with national trends, and exploring six-month service indicators for children who had a Family Group Conference. Implications regarding the reduction of levels of state social work intervention in family life are discussed. Highlights: A local authority used FGCs as part of an approach called Restorative Practice. Notable reductions in social work intervention rates followed. These reductions bucked national trends in England. The significance and implications of these findings are considered.